Clinical Pattern Of Sexually Transmitted Infections And Sexual Behavior In Patients With Genital Symptoms- A Cross Sectional Descriptive Study” - Bhuiyan, Md. Nazrul Islam (Jour Med Resh and Health Sci, 2021)
Background: Sexually transmitted infections (STIs), including human immunodeficiency virus (HIV), continue to present major health, social, and economic problems in the developing world, leading to considerable morbidity, mortality, and stigma. Despite the availability of effective treatment and preventive measures, incidence of STIs is increasing even in developed countries. STIs, acting as a facilitator for the spread of HIV have become a globally important issue at present context. Objectives: To determine the pattern of sexually transmitted infections along with their sexual behaviour in patients presenting with genital symptoms. Material and Methods: A cross sectional, descriptive study was carried out in the department of Dermato-venereology, Medical College for Women & Hospital (MCW&H), Uttara, Dhaka, Bangladesh. During one year period, a total of 130 consecutive cases were enrolled in this study. The diagnosis of infections was made clinically with relevant laboratory investigations and they were interviewed for their sexual behaviour after taking consent and assuring confidentiality. Results: The average age of this population was 27.84 years. Majority belonged to age group 15-24 years, with male to female ratio of 3.19:1. Many (52.3%) were married. The most common infection was condyloma acuminate (29.2%). The mean age of sex debut was 18.95 years and majority (50.8%) belonged to 15-19 years group. The median number of life time partners was 2.0. Only 43 (33.1%) were on monogamous relationship. The 15-34 age groups had maximum number of sexual partners. Married person living singly had more frequent extramarital contact. Only 10 (7.7%) used condom consistently. Conclusions: Younger people should be educated about monogamous relationship along with correct and consistent use of condom for the prevention of STIs.